2010
DOI: 10.4321/s0004-06142010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Tumores retroperitoneales primarios: Revisión de nuestros casos de los diez últimos años

Abstract: Resumen.-OBJETIVO: Estudio de nuestra casuística de tumores retroperitoneales primarios en los últimos 10 años analizando clínica de presentación, pruebas diagnósticas utilizadas, anatomía patológica tumoral, datos quirúrgicos, tratamientos oncológicos complementarios, índices de recidiva y supervivencia. MÉTODOS: Análisis retrospectivo de 37 casos de tumores retroperitoneales primarios diagnosticados en nuestro hospital en los últimos 10 años. RESULTADOS: La TC fue la técnica de imagen más utilizada y con mej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous studies revealed that most of the cases with retroperitoneal masses were actually malignant and 90% of the malignancies were sarcoma, while the common benign tumors included neurogenic tumors, paragangliomas, fibromas, angiomyolipomas, and lipomas (9,30). We found that there were no special and featured findings in laboratory examination for the GN patients.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies revealed that most of the cases with retroperitoneal masses were actually malignant and 90% of the malignancies were sarcoma, while the common benign tumors included neurogenic tumors, paragangliomas, fibromas, angiomyolipomas, and lipomas (9,30). We found that there were no special and featured findings in laboratory examination for the GN patients.…”
Section: Discussionmentioning
confidence: 52%